2017
DOI: 10.1158/0008-5472.can-17-0049
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploid Cell Survival Relies upon Sphingolipid Homeostasis

Abstract: Aneuploidy, a hallmark of cancer cells, poses an appealing opportunity for cancer treatment and prevention strategies. Using a cell-based screen to identify small molecules that could selectively kill aneuploid cells, we identified the compound N-[2-hydroxy-1-(4-morpholinylmethyl)-2-phenylethyl]-decanamide monohydrochloride (DL-PDMP), an antagonist of UDP-glucose ceramide glucosyltransferase. DL-PDMP selectively inhibited proliferation of aneuploid primary mouse embryonic fibroblasts and aneuploid colorectal c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Recent studies have reported the successful targeting of metabolic vulnerabilities which are specific to the tissue-of-origin 16,44 or stem from chromosomal abnormalities 45,46 . We therefore used cBioportal 47,48 to determine copy number amplifications in metabolic genes within our MEC-specific networks in order to identify novel subtype-specific metabolic targets.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported the successful targeting of metabolic vulnerabilities which are specific to the tissue-of-origin 16,44 or stem from chromosomal abnormalities 45,46 . We therefore used cBioportal 47,48 to determine copy number amplifications in metabolic genes within our MEC-specific networks in order to identify novel subtype-specific metabolic targets.…”
Section: Resultsmentioning
confidence: 99%
“…Aneuploid cells from mice bearing a conditional knockout of Mps1 , encoding a mitotic checkpoint kinase, showed a set of significantly overexpressed genes involved in cell metabolism (Foijer et al, 2014). More recently, highly aneuploid colorectal cells were found to be sensitive to an antagonist of ceramide glucosyltransferase due to overabundance of intracellular ceramide, possibly as a result of dysregulated sphingolipid metabolism (Tang et al, 2017). It was also shown that ceramide levels were increased in some aneuploid budding yeast strains and further increasing ceramide levels either genetically or pharmacologically could slow down their proliferation (Hwang et al, 2017).…”
Section: Aneuploidy-associated Stressmentioning
confidence: 99%
“…For example, aneuploid budding yeast have elevated levels of proteotoxic stress, presumably due to the perturbation of the required stoichiometry of protein complexes 19 . Another example is the increased sensitivity of aneuploid yeast to perturbation of sphingolipid metabolism 20,21 . Although some of these findings were successfully recapitulated in mammalian cells 21,22 , the systematic identification of aneuploidy-induced vulnerabilities remains elusive in human cancer.…”
mentioning
confidence: 99%
“…Another example is the increased sensitivity of aneuploid yeast to perturbation of sphingolipid metabolism 20,21 . Although some of these findings were successfully recapitulated in mammalian cells 21,22 , the systematic identification of aneuploidy-induced vulnerabilities remains elusive in human cancer. A major reason for that is that aneuploidy is notoriously difficult to study: it affects multiple genes at once, it plays distinct roles in different contexts, and it is hard to engineer experimentally.…”
mentioning
confidence: 99%